2016
DOI: 10.1109/tuffc.2016.2574801
|View full text |Cite
|
Sign up to set email alerts
|

SAW Characteristics of AlN/SiO2/3C-SiC Layered Structure With Embedded Electrodes

Abstract: A layered structure of aluminum nitride (AlN)/silicon dioxide (SiO)/cubic silicon carbide with embedded electrodes, which enables the growth of high-quality AlN thin films, is proposed and studied. The phase velocity, coupling factor, and temperature coefficient of frequency (TCF) of surface acoustic waves in the proposed structure have been investigated using the finite-element method. The simulation results show that a high velocity of 5485 m/s and a large effective coupling factor ( K) of 1.45% can be simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…This behaviour is described by the temperature coefficient of frequency (TCF) and is hence a crucial parameter and should be as low as possible . As the investigated AlScN samples showed the same temperature dependence as AlN so it can be expected that the TCF for AlScN based devices is similar to AlN based devices and the same well‐established temperature compensation techniques can be used for both AlN and AlScN‐based SAW and BAW devices.…”
Section: Resultsmentioning
confidence: 99%
“…This behaviour is described by the temperature coefficient of frequency (TCF) and is hence a crucial parameter and should be as low as possible . As the investigated AlScN samples showed the same temperature dependence as AlN so it can be expected that the TCF for AlScN based devices is similar to AlN based devices and the same well‐established temperature compensation techniques can be used for both AlN and AlScN‐based SAW and BAW devices.…”
Section: Resultsmentioning
confidence: 99%
“…Such behaviors allowed us to know that it could be used in piezoelectric devices supporting strong electromechanical coupling. Taking an example of a surface acoustic wave resonator using the AlN film layered structure, in our previous work, the authors demonstrated that the effective coupling factor K 2 was dramatically enhanced from 1.45% up to 10.5% by replacing AlN with ScAlN [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Yong's FEM-based periodic analysis only performed DOFs eliminating located on sides of single-finger by using the anti-periodicity boundary conditions, and hence, the remaining part DOFs required to be calculated are still time-consuming. Due to the convenience and visualization of commercial FEM software COMSOL, the built-in quasi-3D FEM model based on COMSOL has drawn great attention [24,40]. To simplify and ensure accuracy, a continuous boundary condition is applied to the two interfaces of the 3D-block in the aperture direction to describe the infinite length of the aperture.…”
Section: Introductionmentioning
confidence: 99%